Ruptured isolated spinal artery aneurysms: a rare manifestation of an arterial dissecting disease - Kee, T. P.; Krings, T.; Pace, J.; Swaminathan, S. K.; Orru', E. (Frontiers in Neurology, 2025)
Isolated spinal artery aneurysms (ISAAs) are a rare cause of intracranial and spinal hemorrhages with unclear pathophysiology and natural history and non-standardized management strategies. We hereby present two cases of ruptured ISAAs of posterior spinal arteries treated with open surgery and embolization, respectively. Case presentations are followed by a comprehensive literature review on ISAA pathophysiology, natural history, and management strategies.